Technical performance of Ethiopian male soccer national team - Hailu, Esayas (ETHIOPIAN JOURNAL OF SPORT SCIENCE, 2021)
The purpose of this study is to explore 2015-2016 technical performance of Ethiopian male soccer national team in reference to African best national team (Algeria) based on the FIFA world national team rank. In this study cross- sectional research design was employed to explore the technical performance of national team. Video of Ten matches played by a Ethiopian (five-match) and Algeria (five- match) for African cup qualification and CECAFA tournaments were sampled from available match footage. Technical performance variables analysis included: Tackle, clearance Interception passes, pass accuracy, crosses, cross accur acy, corner, shot, shot accuracy and goal and players were categorized into three as defence, midfield, and striker based on their position. To this end data were statistically analysed by descriptive statistics, one sample t test and one-way ANOVA and significant is set at p <0.05. The result of this research shows that Ethiopian national team technical performance is significantly behind the Algeria national team on passes, pass accuracy, crosses, cross accuracy, corner, shot, shot accuracy and goal whereas in clearance and Interception inversely Ethiopia is better. Except for crosses in all other technical performances, there is a significant difference among playing position. The finding of this study showed the technical performance of Ethiopian national team is significantly behind African best national team and also on most technical performances there is significant difference among playing position. Therefore, coaches can use this information for establishing technical performance profile of the national team and in designing the training program.